การศึกษาอิทธิพลของอนุภาคโลหะระดับนาโนเมตรต่อกลุ่มโปรตีน - ธีระเดช ขมหวาน (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Nowadays, gold nanoparticles (AuNPs) are widely used in medical research, both in cellular and animal model. However, cytotoxicity and cell signaling pathway after AuNPs treatment are still not well-understood. Thus, this research studied in cell viability and AKT/FOXO3a cell signaling pathway in HepG2 cell line treated by AuNPs (<20 nm). The result showed that AuNPs had cytotoxicity effect on HepG2 in accordance with size, concentration and exposure time of AuNPs treatment. AuNPs at the concentrations of 20 and 40 µg/ml affected disruption of cell shape maintenance, causing cell shrinkage and decreased cell viability after 24 and 48 hours of AuNPs treatment. In addition, AuNPs treatment resulted in increased reactive oxygen species (ROS) generation and reduced AKT protein function, but there was no any change in FOXO3a protein. In conclusion, AuNPs (<20 nm) affected decrease of AKT function, which was involved in ROS generation and cell viability, suggesting as a mechanism used by cell in response to intracellular xenogen for cancer cell viability.